Using Red Oncom (Neurospora Sitophila spp) and Black Oncom (Rhizopus Oligosporus) in feed formulation on Performance and Intestinal Properties of Broiler - Danung Nur Adli; Osfar Sjofjan (Jurnal Nutrisi Ternak Tropis, 2021)
The purpose of this research was to determine the dietary effect of red oncom (Neurospora sitophila spp) and black oncom (Rhizopus oligosporus) on performance and intestinal properties of broiler in different levels. The materials used for this research were 100 unsex broiler (20 days old) with Lohmann strain. Method was used in this experiment was Completely Randomize Design with 5 treatments and 4 replications. The treatment were as follows, T0: basal diet without additive, T1: basal diet + (0.25% red oncom (Neurospora sitophila spp) and 0.25% black oncom (Rhizopus oligosporus), P2: basal diet + (0.5% red oncom (Neurospora sitophila spp) and 0.5% black oncom (Rhizopus oligosporus), T3: basal diet + (0.5% red oncom (Neurospora sitophila spp) and 0.25% black oncom (Rhizopus oligosporus),  and T4: basal diet + (0.75% red oncom (Neurospora sitophila spp) and 0.5% black oncom (Rhizopus oligosporus). The result showed that red oncom (Neurospora sitophila spp) and black oncom (Rhizopus oligosporus) has significantly enhanced (p<0.05) on intestinal properties. It can be concluded that red oncom (Neurospora sitophila spp) and black oncom (Rhizopus oligosporus) in feed gives a positive result on the broiler intestinal properties.